Pathogenesis and methods of diagnosis of chronic kidney disease in cats: retrospective analysis (1981–2007) - Morozenko, Dmytro; Dotsenko, Roman; Vashchyk, Yevheniia; Zakhariev, Andriy; Seliukova, Nataliia; Zemlianskyi, Andrii; Dotsenko, Ekaterina (ScienceRise: Biological Science, 2021)
The aim: to conduct a retrospective analysis of literature sources on the pathogenesis and methods of diagnosis of chronic kidney disease in cats. Materials and methods. The research was conducted by the method of scientific literature open-source analysis: PubMed, Elsevier, electronic resources of the National Library named after V.I. Vernadsky (1981–2007). Results. Chronic kidney disease is a common reason for cat owners to go to veterinary clinics. The term “chronic kidney disease” has a broader meaning than the more limited and not very specific name – chronic renal failure; it is also used to indicate the preazotemic stage of the disease. Chronic kidney disease is characterized by a gradual deterioration of the clinical condition of animals due to progressive decline in renal function. An idea of the pathogenesis and methods of diagnosis of chronic kidney disease in the period from 1981 to 2007 is presented. Conclusions. According to the results of retrospective analysis of literature sources for the period from 1981 to 2007, the basis was identified aspects of the pathogenesis of chronic kidney disease in domestic cats, which have not lost relevance today. The main link during chronic kidney disease in cats is the development of hyperazotemia and, as a consequence, endogenous intoxication of the body, which develops gradually and leads to the death of the animal. The morphological basis of chronic kidney disease in cats is the development of diffuse nephrosclerosis, which is reflected in the results of clinical, biochemical and instrumental studies. According to biochemical analysis of blood, in cats recorded an increase in urea and creatinine, the results of clinical studies of urine showed a decrease in its relative density, as well as the development of proteinuria, the appearance of erythrocytes and cylinders. According to the results of hematological research, anemic syndrome develops due to decreased erythropoietin synthesis. With age in cats, ultrasound examination of the kidneys reveals a decrease in their volume due to uniform sclerosis of the parenchyma: it is determined by its thinning and increased echogenicity due to the accumulation of connective tissue components, which is a sign of nephrosclerosis. Although kidney biopsy is the most informative method of diagnosing chronic kidney disease, it has many contraindications, which does not allow its use in the routine diagnosis of nephropathy in domestic cats. its thinning and increase in echogenicity due to the accumulation of connective tissue components, which is a sign of nephrosclerosis, is determined. Although kidney biopsy is the most informative method of diagnosing chronic kidney disease, it has many contraindications, which does not allow its use in the routine diagnosis of nephropathy in domestic cats. Its thinning and increase in echogenicity due to the accumulation of connective tissue components, which is a sign of nephrosclerosis, is determined